Strategi Peningkatan Daya Saing Tuna Olahan Indonesia di Pasar Internasional - Wiji Lestari; Rizal Syarief; Komar Sumantadinata (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
Tuna Indonesia mostly exported in fresh and frozen (55%), and 45% in processed tuna. It is therefore necessary to study the competitiveness of processed tuna. The method used is the Revealed Comparative Advantage (RCA) and the analysis of the Competitive Profile Matrix (CPM) Analysis, In the year 2006 to 2010, Indonesia has a fresh tuna RCA index between 4.56 to 8.18, tuna frozen at 0.49 to 1,43 and processed tuna fish ranged from 1.25 to 2.68. Based on the analysis of the competitive profile, three factors of production and marketing of highly influential on the competitiveness of tuna fish are (1) the quality of the resulting processed tuna fish with a weight of 0.143, (2) tariff and non tariff barriers with a weight of 0.114, and (3) Development and Promotion Intellegence market with the weight of 0.110. As for the human and institutional factors, factors which have an important role in increasing competitiveness is (1) The Role of Government in the development of the tuna processing industry with a weight of 0.147, (2) Availability of human resources capable of handling quality with weights 0.135, and (3) the role of government in the prevention and handling of illegal fishing by weight of 0.130. Based on the analysis of RCA analysis and matrix analysis of the competitive profiles of priority strategies that can be done to improve the competitiveness of Indonesia's processed tuna to the factors of production and marketing are as follows (1) Improve the quality of processed tuna Indonesia; (2) Encourage overcome tariff and non tariff barriers; (3) enhance market development and promotion Intellegence, The strategic priorities for the human and institutional factors are (1) Increase the Role of Government in the development of the tuna processing industry, (2) Improving the human resources capable of handling quality, (3) Eradication and control of illegal fishing.